Pengaruh Promosi dan Online Customer Review terhadap Minat Beli Konsumen Pada Lazada - Ni Luh Putu Vivi Aryantini; I Wayan Suwendra (Ekuitas: Jurnal Pendidikan Ekonomi, 2026)
This study aims to determine the effect of promotion and online customer reviews on consumer purchasing interest on Lazada. The study uses a quantitative approach with a causal design. Research data were obtained through the distribution of questionnaires to 140 respondents who are residents of Buleleng Regency and have made purchases through Lazada. The sampling technique used was non-probability sampling with a purposive sampling method. The results show that (1) promotion affects consumer purchase intention, (2) online customer reviews affect consumer purchase intention, (3) promotion and online customer reviews affect consumer purchase intention on Lazada. The coefficient of determination value shows that the promotion and online customer review variables are able to explain the influence on consumer purchase intention, while the remaining portion is influenced by other factors outside the study. Based on the results, sellers and the Lazada platform are advised to improve more attractive promotional strategies and continuously boost consumer trust and purchasing interest.